2022
DOI: 10.3389/fpubh.2022.847696
|View full text |Cite
|
Sign up to set email alerts
|

Health Disparities in Pharmacy Practice Within the Community: Let's Brainstorm for Solutions

Abstract: Health disparity is defined as a type of health difference that is closely linked with social, economic and/or environmental disadvantage. Over the past two decades, major efforts have been undertaken to mitigate health disparities and promote health equity in the United States. Within pharmacy practice, health disparities have also been identified to play a role in influencing pharmacists' practice across various clinical settings. However, well-characterized solutions to address such disparities, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…Targeted approaches, accounting for regional differences, can help pharmacists in less favorable regions improve their financial practices and, therefore, their overall financial performance. These potential solutions can inform regional support systems and policies to address disparities and improve financial practices, in line with previous research findings [40,41].…”
Section: Plos Onesupporting
confidence: 77%
“…Targeted approaches, accounting for regional differences, can help pharmacists in less favorable regions improve their financial practices and, therefore, their overall financial performance. These potential solutions can inform regional support systems and policies to address disparities and improve financial practices, in line with previous research findings [40,41].…”
Section: Plos Onesupporting
confidence: 77%
“…However, there is a plethora of literature about existing healthcare disparities in pharmacy practice. These disparities stem from structural inequity, social determinants of health, and practitioner-based biases towards marginalised and socially excluded populations (Hurley-Kim et al, 2022 ; Wenger et al, 2016 ). The WHO (World Health Organisation), lists many social determinants which can influence health equity, such as socioeconomic status, education, housing, food, social inclusion and non-discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…This can be achieved by tailoring interventions and solutions at the organisational level towards gaps in knowledge of pharmacists towards marginalised populations. Such interventions should target the enhancement of the role of pharmacists in addressing and understanding social determinants of health, starting with social inclusion and non-discrimination (Foster et al, 2021 ; Hurley-Kim et al, 2022 ; Kiles et al, 2022 ; Wenger et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies in the United States and globally have revealed disparities in pharmacy services and medication management in term of access to and utilization of guideline‐recommended medications, medication accessibility and affordability, medication adherence, and understanding of diseases, medications, and healthy lifestyles 3‐11 . Pharmacists are members of the multidisciplinary health care team and are well positioned to help reduce health disparities through education, medication therapy, and improving access to care 12,13 . They are often the most accessible health care provider in many countries, and pharmacists' roles have broadened and continue to undergo dynamic changes globally.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11] Pharmacists are members of the multidisciplinary health care team and are well positioned to help reduce health disparities through education, medication therapy, and improving access to care. 12,13 They are often the most accessible health care provider in many countries, and pharmacists' roles have broadened and continue to undergo dynamic changes globally. The pharmacist's role varies from operational responsibilities such as medication dispensing and order verification to direct patient care in immunization delivery and pointof-care testing.…”
Section: Introductionmentioning
confidence: 99%